Identifikasi Plant Purwarupa Heat Exhcanger Tipe Shell dan Tube Model Counter Flow Memanfaatkan Software Matlab - Hairil Budiarto; Faikul Umam (Jurnal Teknik Mesin, 2018)
Abstract – a heat exchanger is a device that acts as a transfer of heat energy between two fluids or more. There are various ways to improve the effectiveness of heat exchange devices, according to mechanical engineering, by increasing the convection heat transfer coefficient, increasing the surface area of the heat exchanger and increase the temperature difference to reach the specified temperature. The heat transfer can be defined as the transfer of energy from one system to another as a result of the temperature difference, this energy transfer always occurs from a high temperature system to another lower temperature system and will stop after the two systems reach the same temperature, the temperature difference is the main requirement for the transfer of the system. The design of prototype heat exchanger coolermodel counter flow has been made and by utilizing MATLAB software, we have obtained mathematical model of plant order 2, to test the response of plant using simulink in MATLAB, so that the response of the plant at setpoint is still above, improve the performance or response of the plant..Keywords: